Protecting the “Homo Digitalis” - Ninet, Antoni Abat (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2019)
This paper analyses from a legal and philosophical perspective the appearance of a new human species, the so-called Homo Digitalis, a Homo Sapiens permanently interconnected with others throughout I.T devices. Twenty-four hours a day. Three hundred and sixty-five days a year, living in a world of ones and zeros. We all are inexorably the new-born Homo Digitalis, or as some authors define it, post-humans, and there is no possible opposition to this Darwinist evolution, or between the Homo digitalis and other citizens. The first section deals with the relationship between technique (τεχνη), technology and humanity, a relation that is ancient as philosophy. The starting point is the pre-Socratic philosophers, Plato and Aristotle, and it ends by analysing the relation of the three concepts in modernity and post-modernity (Weber, Heidegger and Marcuse). The second section deals with the definition of the Homo Digitalis from an evolution of Sartori´s Homo Videns. The paper ends by exposing the latest judicial decisions, domestic and international legislation to protecting citizens (as new-born Homo Digitalis) from wrongful use of technology.